On the borders of world-system : contact zones in ancient and modern times - Margaryan, Ervand, 1961- (Archaeopress Archaeology, 2020)
This title examines the historical, archaeological, and political interpretations of world-systems theory and geocivilisational analysis. The macrosociological issues of ancient and modern history are presented through five case-studies, concentrating on the Taurus-Caucasus region, which functioned as a contact zone throughout the different periods.